Determining the Quantitative Principles of T Cell Response to Antigenic Disparity in Stem Cell Transplantation - Salman, Ali; Koparde, Vishal; Hall, Charles E.; Jameson-Lee, Max; Roberts, Catherine; Serrano, Myrna; AbdulRazzaq, Badar; Meier, Jeremy; Kennedy, Caleb; Manjili, Masoud H.; Spellman, Stephen R.; Wijesinghe, Dayanjan; et al. (Frontiers in Immunology, 2018)
Alloreactivity compromising clinical outcomes in stem cell transplantation is observed despite HLA matching of donors and recipients. This has its origin in the variation between the exomes of the two, which provides the basis for minor histocompatibility antigens (mHA). The mHA presented on the HLA class I and II molecules and the ensuing T cell response to these antigens results in graft versus host disease. In this paper, results of a whole exome sequencing study are presented, with resulting alloreactive polymorphic peptides and their HLA class I and HLA class II (DRB1) binding affinity quantified. Large libraries of potentially alloreactive recipient peptides binding both sets of molecules were identified, with HLA-DRB1 presenting an order of magnitude greater number of peptides. These results are used to develop a quantitative framework to understand the immunobiology of transplantation. A tensor-based approach is used to derive the equations needed to determine the alloreactive donor T cell response from the mHA-HLA binding affinity and protein expression data. This approach may be used in future studies to simulate the magnitude of expected donor T cell response and determine the risk for alloreactive complications in HLA matched or mismatched hematopoietic cell and solid organ transplantation.